Physical and chemical characterization and bioactive compounds from blackberry under calcium chloride application - Modesto, Joyce Helena [UNESP]; Azevedo Souza, Jackson Mirellys [UNESP]; Ferraz, Rafael Augusto [UNESP]; Silva, Marcelo de Souza [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
Calcium chloride application on fruits maintains the firmness of fruits, decreases storage breakdown and rot, extends shelf-life, and increases vitamin C and calcium content. Blackberries have low post-harvest durability due to the intrinsic characteristics of their fruits, mainly the high respiratory rate and low firmness, which causes problems in the production chain of fresh fruits. The current study aimed to evaluate the effects of pre-harvest application of calcium chloride on the fruits of 'Tupy' blackberry (Rubus spp.). A randomized block design for a factorial scheme was used, i.e. calcium chloride concentrations (0, 1.5, 3, and 4.5%) and number of applications (1, 2, and 3). Multiple applications occurred between 5-day intervals. The results showed that the calcium content in the fruits increased with a single application of 2.2%, but a decrease in mass loss was observed with a 4.5% application. The results also indicated great firmness and ascorbic acid content of fruits of 'Tupy' blackberry, in addition to the significant increase in fruit size and mass. However, in general, the content of soluble solids, sugars, antioxidant activity and total polyphenols decreased.
Keywords: Rubus spp.; fruit texture; nutritional value; Ca+2; phenolic compounds; antioxidant activity